Nutritional and dietary assessment of cadets menus at the Iran Army Military Academy - Reza Sabzevari Rad (Discover Food)
Abstract Background Regarded among the most important pillars of health, healthy nutrition has the greatest impact on military forces’ mental and physical condition. Apart from the adverse effects this might have on a person’s health, lack and overconsumption of macro and micronutrients will cause a loss of material wealth. Consequently it’s important to avoid wasting resources and its adverse impacts. Methodology Random samples of 150 male cadets (age: 21.20 ± 7.8 years, height: 176.7 ± 6.6 cm, body mass: 76.5 ± 9.6 kg, BMI: 24.5 ± 2.8 kg/m2) were taken in this descriptive cross-sectional research. Data collection relied on demographic data, international physical activity questionnaire (IPAQ), and food frequency based on food frequency questionnaire (FFQ). Under a significance level of less than 0.05, the gathered data were mathematically evaluated using an independent T-test within SPSS-20 program. Result The study’s findings suggested that dietary intake of energy expenditure, protein, linolenic acid (omega3), linoleic acid (omega 6), fiber intake, water, vitamins A, D, C, E, B1, B5, B6 B9, B12, H, choline, potassium, calcium, iron, phosphorus, zinc, magnesium, copper, selenium, manganese, fluorine, chromium, molybdenum, boron, cobalt, nickel was below MDRI (p = 0.001). which can lead to problems with the absence of macronutrients and micronutrients. Furthermore, the energy intake, carbohydrates, lipids, vitamins K, B2, B3, sodium, chlorine, and iodine were more than that of MDRI (p = 0.001), which will adversely affect cadets’ health and loss of material resources. Conclusion For the overall health and performance of military students, it’s vital that their energy balance and nutritional requirements including macronutrients, vitamins, and minerals be evaluated and an accurate and suitable diet be formulated. Consequently, using supplements or adding nutrient-rich food categories including vitamins and minerals in their diet becomes an obvious necessity to avoid side effects and resource wastage.